2017
DOI: 10.1007/s11101-017-9507-3
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidins: a comprehensive review encompassing structure elucidation via mass spectrometry

Abstract: Procyanidins are polyphenols abundant in dietary fruits, vegetables, nuts, legumes, and grains with a variety of chemopreventive biological effects. Rapid structure determination of these compounds is needed, notably for the more complex polymeric procyanidins. We review the recent developments in the structure elucidation of procyanidins with a focus on mass spectrometric approaches, especially liquid chromatography-tandem mass spectrometry (LC-MS/MS) and matrix-assisted laser desorption ionization (MALDI) MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
188
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(199 citation statements)
references
References 91 publications
(119 reference statements)
8
188
1
2
Order By: Relevance
“…Depending on the type of monomers, PACs can be classified into procyanidins, prodelphinidins, and propelargonidins. The most abundant group, procyanidins, consists exclusively of (+)-catechin and (−)-epicatechin monomers [77]. Prodelphinidins and propelargonidins are composed of (−)-gallocatechin/(−)-epigallocatechin and (+)-afzelechin/(−)-epiafzelechin monomers, respectively [75], and have a more limited distribution.…”
Section: Pacs: Chemical Structure Occurrence and Intakementioning
confidence: 99%
“…Depending on the type of monomers, PACs can be classified into procyanidins, prodelphinidins, and propelargonidins. The most abundant group, procyanidins, consists exclusively of (+)-catechin and (−)-epicatechin monomers [77]. Prodelphinidins and propelargonidins are composed of (−)-gallocatechin/(−)-epigallocatechin and (+)-afzelechin/(−)-epiafzelechin monomers, respectively [75], and have a more limited distribution.…”
Section: Pacs: Chemical Structure Occurrence and Intakementioning
confidence: 99%
“…However, under low nitrate conditions, we did not find any change in denitrification rates between F. x bohemica and native species. Procyanidins are known to be complex polymeric polyphenols [48] that are potentially costly for F. x bohemica in limited nitrate conditions and are thus produced less in stressful conditions or are dependent on the developmental stage of the plants. Another explanation could be that produced procyanidins were ineffective in our experimental conditions because, for instance, they were sorbed into the soil or degraded.…”
Section: Impacts Of Knotweed On Soil N-functions and Microbial Communmentioning
confidence: 99%
“…Depending on the type of monomers, PACs can be classified into procyanidins, prodelphinidins, and propelargonidins. The most abundant group, procyanidins, consists exclusively of (+)-catechin and (À)epicatechin monomers [47]. Prodelphinidins and propelargonidins are composed of (À)-gallocatechin/(À)-epigallocatechin and (+)-afzelechin/(À)-epiafzelechin monomers, respectively [45], and have a more limited distribution Dietary assessment studies have shown that PACs, especially procyanidins are among the most abundant polyphenols in the human diet [6], as they are present in a variety of botanical sources and plant food products such as tea, fruits, nuts, cacao products, legumes, and cereal grains [1,2].…”
Section: Pacs: Chemical Structure Occurrence and Intakementioning
confidence: 99%
“…In these studies, the median lethal dose (LD50) was found to be greater than 5000 mg kg À1 bw (HED of ≈50 g) when administered once by oral gavage, and 1400-2000 mg kg À1 d À1 (HED of ≈14-20 g d À1 ) was found to be the no-observed-adverse-effect level (NOAEL) for systemic toxicity in sub-chronic administration. A recent study evaluated the safety and tolerability of GSPE intake (up to 2.5 g d À1 ) in a small number of healthy adults for a 4-week period and found a good tolerability without adverse effects on hematological or biochemical parameters [47].…”
Section: Clinical Trialsmentioning
confidence: 99%